Distinctive in vitro ATP Hydrolysis Activity of AtVIPP1, a Chloroplastic ESCRT-III Superfamily Protein in Arabidopsis - Ohnishi, Norikazu; Sugimoto, Manabu; Kondo, Hideki; Shioya, Ken-ichi; Zhang, Lingang; Sakamoto, Wataru (Frontiers in Plant Science, 2022)
Vesicle-inducing protein in plastid 1 (VIPP1), characteristic to oxygenic photosynthetic organisms, is a membrane-remodeling factor that forms homo-oligomers and functions in thylakoid membrane formation and maintenance. The cyanobacterial VIPP1 structure revealed a monomeric folding pattern similar to that of endosomal sorting complex required for transport (ESCRT) III. Characteristic to VIPP1, however, is its own GTP and ATP hydrolytic activity without canonical domains. In this study, we found that histidine-tagged Arabidopsis VIPP1 (AtVIPP1) hydrolyzed GTP and ATP to produce GDP and ADP in vitro, respectively. Unexpectedly, the observed GTPase and ATPase activities were biochemically distinguishable, because the ATPase was optimized for alkaline conditions and dependent on Ca2+ as well as Mg2+, with a higher affinity for ATP than GTP. We found that a version of AtVIPP1 protein with a mutation in its nucleotide-binding site, as deduced from the cyanobacterial structure, retained its hydrolytic activity, suggesting that Arabidopsis and cyanobacterial VIPP1s have different properties. Negative staining particle analysis showed that AtVIPP1 formed particle or rod structures that differed from those of cyanobacteria and Chlamydomonas. These results suggested that the nucleotide hydrolytic activity and oligomer formation of VIPP1 are common in photosynthetic organisms, whereas their properties differ among species.